Elastic Sponges: Hydrophilic Sponges for Leaf‐Inspired Continuous Pumping of Liquids (Adv. Sci. 6/2017). Issue 6 (June 2017) - Zhou, Tingjiao; Yang, Jinbin; Zhu, Deyong; Zheng, Jieyao; Handschuh‐Wang, Stephan; Zhou, Xiaohu; Zhang, Junmin; Liu, Yizhen; Liu, Zhou; He, Chuanxin; Zhou, Xuechang
Abstract : In article number1700028, Xuechang Zhou and co‐workers describe a leaf‐like pumping strategy by mimicking the transpiration process through leaves for autonomous and continuous liquid transport enabled by durable hydrophilic sponges. Highly‐defined flow patterns, chemical gradients, and "stop‐flow" manipulation of the flow were achieved by simply integrating the sponges to microfluidic devices.